Movable-crosslinking tough hydrogels with lithium ion as sensitive and durable compressive sensor. (1st February 2021) - Wu, Zhujian; Zhang, Jiajie; Lin, Qingqing; Zhu, Yutian; Wang, Lian; Li, Yongjin
Abstract: Hydrogel has great potential application in soft wearable electronics as flexible sensors for healthcare and motion detection. However, these applications are generally limited due to its weak mechanical properties including strength, stretchability and recoverability. Herein, we report a tough hydrogel sensor with hydrogen-bonding network and slidable crosslinking which is composed of acrylic acid (AAc), N, N -Dimethylacrylamide (DMAA) and polyrotaxane cross-linker (PR-AC) as compressive sensor through a simple and straightforward strategy. Attributed to the synergistic effect of the hydrogen bonds network and slidable crosslinking, the as-prepared hydrogel exhibits outstanding stretchability (755%–992%), excellent recoverable performance (hysteresis area <71.3 kJ/m 3 ), and high compressive strength (9.5 MPa). The Li-ion based hydrogels shows high sensitive response to a wide range of compressive strain (5%–50%), which can be utilized to detect human motions such as fingers, knees and even steps. More importantly, the prepared sensor exhibits stable and repeatable resistance change upon large deformation after 100 cyclic uniaxial compression. Considering the low cost and feasibility of fabrication process, this hydrogel provides a desirable concept for transparent flexible sensors with high requirements on mechanical properties. Graphical abstract: Image 1 Highlights: Hydrogel with conductivity was fabricated through a one-step and straightforward strategy. Hydrogel exhibits excellent mechanical property due to sliding crosslink and hydrogen bonds. Hydrogel strain sensor shows sensitivity and stability upon both large and subtle deformation.